A ética feminista e os direitos humanos fundamentais na perspectiva de gênero: igualdade na diferença e no reconhecimento de identidades alterais - Miyamoto, Yume Maria Helena (2012)
This study investigates how feminist ethics can promote fundamental human rights with a gender perspective from multiple dialectical. Human rights has in its base a perception of the male world need to be sensitive to acknowledge the other from its history, from its social context, their culture, their differences. If, at first, humanity experienced the tragic treatment difference to allow, within the law, the atrocities of the Holocaust, has evolved to include all human beings the right of equality treating the individual in the abstract to the point it does not come to be recognizes by his fellow, having seen an urgent course correction in order to recognize their differences. However, none of this makes sense without the debate on male hegemonic vision right, discusses the possibility of ethics itself be contaminated with the male vision of the point of obscuring the vision of the woman herself, since she should be seeing the world from the perspective male. Becomes necessary, then the reflection through multiple dialectical a feminist ethics that accounts for all the gains made by the movements of struggle for the liberation of women to provide human rights from the perspective of gender. It is the impact of gender studies to the understanding of fundamental human rights. The dialogue with Nancy Fraser’s reflections o the redistribution of economic resources in unequal societies, since gender justice strives of the distributive discusses complemented with issues of representation, identity and difference. The focus of our reflections focused of feminist politics that were previously focused on labor and violence and now struggles to adjust its focus on gender identity, showing how relevant it is to build a democratic society in particular respect to fundamental human rights. Moreover, the analysis of the relationships between feminism and social practices currents must be made from its duality, ie, the impact of feminism on the perceptions, behaviors and social institutions and the impact of these on the feminist movement. The contribution of this work towards the recognition if identities and differences in gender issues and to enrich the critical theory of fundamental human rights, innovative research in the area of law in a gender perspective since they have as a common thread for feminist ethics understanding of human rights, to reach the core of the fundamental rights and guaranties for their participation in the construction of a new humanistic culture, to defend the values of the woman person, since the genre study aims to unveil the struggles of women to see effected fundamental human rights through multiple dialectical.